Does corporate environmental responsibility contribute to financial performance? A dual path analysis through operational efficiency and the cost of debt. (17th August 2022) - Gao, Lan; Wan, Liang
Abstract: Given the growing environmental awareness among stakeholders, firms are increasingly been asked to act in an environmentally responsible manner. However, the relationship between corporate environmental responsibility (CER) and corporate financial performance is quite mixed. This study aims to examine the impact of CER on financial performance and explores the mediating effects of operational efficiency and the cost of debt. A firm‐level panel data of 2173 Chinese listed firms are analyzed. The results show that efforts and investments in CER positively and directly affect financial performance. Operational efficiency and cost of debt mediate the relationship between CER and financial performance. This study contributes to the stakeholder theory and highlights that CER can promote corporate financial performance by improving operational efficiency and reducing the cost of debt. This study also has practical implications and highlights the importance of enhancing operational management and information communication in the course of CER practices.